2014
DOI: 10.4236/aar.2014.32011
|View full text |Cite
|
Sign up to set email alerts
|

Ability of Comprehensive Geriatric Assessment to Detect Frailty

Abstract: Background and Aim of the Work: Frailty is a state of reduced physiological reserve associated with increased susceptibility to disability. It is associated with a high morbidity and mortality. This work assessed the ability of comprehensive geriatric assessment to detect frailty in elderly patients. Subjects and Methods: A total number of 104 elderly patients (above 60 years old) were included in this study and they were subjected to a comprehensive geriatric assessment (CGA) including: (history and full clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
1
0
0
Order By: Relevance
“…In a study by Gregg et al 17 , which included 6,588 residents aged 60 and over, it was reported that 32% of diabetic women and 15% of men with diabetes did not have the capacity to walk a quarter of a mile, do housework or climb stairs, this rate for those without diabetes was detected as 14% for women and 8% in men. In a study by Amer et al 18 in which 104 elderly patients were included, similar to our study, it was seen that in physically frail cases the rate of associated chronic diseases, diabetes, ischemic heart diseases, hypertension, stroke, vision and hearing loss was significantly higher than others.…”
Section: Discussionsupporting
confidence: 87%
“…In a study by Gregg et al 17 , which included 6,588 residents aged 60 and over, it was reported that 32% of diabetic women and 15% of men with diabetes did not have the capacity to walk a quarter of a mile, do housework or climb stairs, this rate for those without diabetes was detected as 14% for women and 8% in men. In a study by Amer et al 18 in which 104 elderly patients were included, similar to our study, it was seen that in physically frail cases the rate of associated chronic diseases, diabetes, ischemic heart diseases, hypertension, stroke, vision and hearing loss was significantly higher than others.…”
Section: Discussionsupporting
confidence: 87%